STUDI ANATOMI DAUN DAN BATANG Maesopsis eminii (Rhamnaceae) - Eka Fatmawati Tihurua; Sunaryo (The East Java Biological Society, 2012)
Maesopsis eminii is one of alien and invasive plant in Indonesia and planted in Resort Bodogol, Gunung Gede Pangrango National Park. The results showed M. eminii has dorsiventral and hypostomatic leaf type with anomocytic stomata, drusse type of CaCO3 crystal, multicellular and uniseriate trichomes in the upper and lower surface. While its stem has variation in its ray initial layer depend on its trunk circumference.